Characterizing the financial cycle: Evidence from a frequency domain analysis - Till Strohsal; Christian Proa\~no Acosta; Jürgen Wolters (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
A growing body of literature argues that the financial cycle is considerably longer in duration and larger in amplitude than the business cycle and that its distinguishing features became more pronounced over time. This paper proposes an empirical approach suitable to test these hypothe- ses. We parametrically estimate the whole spectrum of financial and real variables to obtain a complete picture of their cyclical properties. We provide strong statistical evidence for the US and slightly weaker evidence for the UK validating the hypothesized features of the financial cycle. In Germany, however, the financial cycle is, if at all, much less visible.
Keywords: C22; E32; E44; 330; Financial Cycle; Business Cycle; Indirect Spectrum Estimation; Bootstrapping Inference